2014
DOI: 10.1371/journal.pone.0106608
|View full text |Cite
|
Sign up to set email alerts
|

Gi Proteins Regulate Adenylyl Cyclase Activity Independent of Receptor Activation

Abstract: Background and purposeDespite the view that only β2- as opposed to β1-adrenoceptors (βARs) couple to Gi, some data indicate that the β1AR-evoked inotropic response is also influenced by the inhibition of Gi. Therefore, we wanted to determine if Gi exerts tonic receptor-independent inhibition upon basal adenylyl cyclase (AC) activity in cardiomyocytes.Experimental approachWe used the Gs-selective (R,R)- and the Gs- and Gi-activating (R,S)-fenoterol to selectively activate β2ARs (β1AR blockade present) in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…1e,f ). We also observed a well-documented increase of sensitivity to ISO after PTX treatment which might be due to off-target effects of this toxin 16 . To further test the hypothesis that atropine can mediate cardiac effects independent of muscarinic receptor blockade, we isolated ventricular cardiomyocytes from M 2 - or M 1/3 -receptor knockout mice 17 , 18 and expressed the cAMP-FRET sensor in these cells by adenoviral gene transfer.…”
Section: Resultssupporting
confidence: 60%
“…1e,f ). We also observed a well-documented increase of sensitivity to ISO after PTX treatment which might be due to off-target effects of this toxin 16 . To further test the hypothesis that atropine can mediate cardiac effects independent of muscarinic receptor blockade, we isolated ventricular cardiomyocytes from M 2 - or M 1/3 -receptor knockout mice 17 , 18 and expressed the cAMP-FRET sensor in these cells by adenoviral gene transfer.…”
Section: Resultssupporting
confidence: 60%
“…The possible explanation for this phenomenon is that the mammals express nine membranous AC isoforms (ACs 1–9) and a soluble AC (sAC). Among these AC isoforms and sAC, only ACs‐5 and ACs‐6 were found to be regulated by Gα protein (Hanoune and Defer, ; Melsom et al, ). Thus, the changes on the contents of AC in response to arsenite exposure may not be more sensitive than the alteration of Gα protein as well as the PKA or cAMP contents.…”
Section: Discussionmentioning
confidence: 99%
“…The faster response to 1 µM FSK in all Epac1-CB2-HEK cell response types as compared to Epac1-HEK cells might indicate that heterologous CB2 expression alters the available G-protein pool. It has been reported that free Gαi subunits can cause effects at ACs that are independent of receptor activation [ 32 ]. Through the presence of, e.g., spontaneously inactive CB2 that couple Gαi subunits [ 33 ], but do not elicit a signaling response, the pool of free Gαi might be reduced, leading to a faster cAMP production after direct AC activation with FSK in Epac1-CB2-HEK cells.…”
Section: Discussionmentioning
confidence: 99%